CD4+ T cells from patients with primary sclerosing cholangitis exhibit reduced apoptosis and down-regulation of proapoptotic Bim in peripheral blood. Issue 2 (14th September 2016) - Schoknecht, Tanja; Schwinge, Dorothee; Stein, Stephanie; Weiler-Normann, Christina; Sebode, Marcial; Mucha, Sören; Otto, Benjamin; Ellinghaus, Eva; Stahl, Felix; Franke, Andre; Lohse, Ansgar W; Herkel, Johannes; et al.
Abstract: The pathogenesis of the progressive liver disease, primary sclerosing cholangitis (PSC), remains largely elusive. The strong genetic association with HLA loci suggests that T cell–dependent, adaptive immune reactions could contribute to disease pathogenesis. Recent studies have indicated that PSC is also associated with polymorphisms in the locus encoding for proapoptotic Bim ( BCL2L11 ). Bim is crucial for the maintenance of immunologic tolerance through induction of apoptosis in activated T cells. Of interest with regard to PSC is the finding that BCL2L11 -deficient mice develop periductular infiltrates. We, therefore, investigated, whether defective apoptosis of T cells might contribute to the phenotype of PSC. Thus, we induced apoptosis of T cells from patients with PSC and controls by repeated T cell receptor (TCR) stimulation or cytokine withdrawal. We found that CD4 + T cells, but not CD8 + T cells, from patients with PSC exhibited significantly reduced apoptosis in response to both, TCR restimulation or cytokine withdrawal. This increased apoptosis resistance was associated with significantly reduced up-regulation of proapoptotic Bim in T cells from patients with PSC. However, T cell apoptosis did not seem to be influenced by the previously described BCL2L11 polymorphisms. Reduced CD4 + T cell apoptosis in patients with PSC was not due to reduced cell activation, as indicated by a similar surface expression of the activation markers CD69, CD25, and CD28 in T cells from patients and controls. Thus, decreased apoptosis of activated CD4 + T cells may be part of the immune dysregulation observed in patients with PSC.